Analisis Risiko Keselamatan Kerja dan Kesehatan Lingkungan Akibat Proses Pengecatan Pesawat di Hangar PT. XYZ - Aziz Fauzan Allaam; Yogi Prisma Caysar Pradewa (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
The study aims to analyze the occupational safety and environmental health risks due to aircraft painting at the Hangar of PT. XYZ. The study is a descriptive study with a qualitative approach. The results of the study are the analysis of occupational safety risks seen from occupational safety risks and risk control. Occupational safety risks in aircraft painting activities at PT. XYZ are divided into several parts, namely (1) Exposure to hazardous chemicals is included in the high category; (2) The risk of work accidents is included in the moderate category; (3) Equipment damage is included in the low category; and (4) Fire is included in the low category. Risk control can be carried out by (1) Increasing strict supervision of the aircraft painting process; (2) Conducting appropriate occupational safety training for workers; (3) Using PPE; (4) Using adequate safety equipment; and (5) Carrying out proper equipment maintenance. The analysis of environmental health risks is seen from environmental health risks, sources of risk and risk control. Environmental health risks are divided into several parts, namely (1) Air pollution is included in the moderate category; (2) Soil and water contamination is included in the moderate category; and (3) Environmental damage is included in the moderate category. Sources of environmental health risks are the use of hazardous chemicals and painting waste. Risk control can be done by carrying out strict supervision, using safe chemicals and proper waste management.